2020
DOI: 10.3390/ijerph17176294
|View full text |Cite
|
Sign up to set email alerts
|

Can Haematological and Hormonal Biomarkers Predict Fitness Parameters in Youth Soccer Players? A Pilot Study

Abstract: The study aimed to investigate the correlations among immune, haematological, endocrinological markers and fitness parameters, and assess if the physiological parameters could be a predictor of fitness values. Anthropometric, physical evaluations (countermovement jump—CMJ, 10 m sprint, VO2max, repeated sprint ability—RSA total time and index) and determination of blood (IL-6, IL-10, IL-17A and tumour necrosis factor) and salivary (testosterone and cortisol) samples parameters in 28 young male soccer players (a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 57 publications
(72 reference statements)
0
7
0
2
Order By: Relevance
“…En la actualidad, VO 2 máx, la respuesta de la frecuencia cardiaca y presión arterial, entre otros, permiten valorar y graduar el entrenamiento deportivo. 21,22 El presente estudio cumple con el objetivo de caracterizar valores de referencia de jugadoras de soccer en condiciones basales, antes de un juego competitivo. También permite apreciar las respuestas de variables hemáticas (citometría hemática), proinflamatorias y metabólicas como respuesta a un partido de fútbol, al destacar los límites como producto del esfuerzo en un juego, así como los valores mínimos esperados, los cuales se asocian frecuentemente a la intensidad del esfuerzo.…”
Section: Discussionunclassified
“…En la actualidad, VO 2 máx, la respuesta de la frecuencia cardiaca y presión arterial, entre otros, permiten valorar y graduar el entrenamiento deportivo. 21,22 El presente estudio cumple con el objetivo de caracterizar valores de referencia de jugadoras de soccer en condiciones basales, antes de un juego competitivo. También permite apreciar las respuestas de variables hemáticas (citometría hemática), proinflamatorias y metabólicas como respuesta a un partido de fútbol, al destacar los límites como producto del esfuerzo en un juego, así como los valores mínimos esperados, los cuales se asocian frecuentemente a la intensidad del esfuerzo.…”
Section: Discussionunclassified
“…Ten milliliters of blood were drawn from either the participants’ left or right median cubital vein. The blood was centrifuged at 3000 rpm for 10 min, and the upper layer of serum was stored in a −80 °C freezer [ 27 ]. After blood was drawn, urine and saliva were collected from the participants.…”
Section: Methodsmentioning
confidence: 99%
“…Various studies have shown a large to very large association of fitness parameters with training load (Nobari et al, 2020a , c ) and endocrine markers (Mejri et al, 2005 ; Hammami et al, 2018 ; Perroni et al, 2020 ) in young soccer players. Therefore, the results were analyzed to obtain a sample size with at least 0.9 power.…”
Section: Methodsmentioning
confidence: 99%